Genetic Variability and Combining Abilities for Earliness to Nut Yield and Nut Weight in Selected Cashew (Anacardium Occidentale L.) Clones. Issue 1 (31st December 2022) - Adu-Gyamfi, Paul K. K.; Barnnor, Michael; Akpertey, Abraham; Padi, Francis
ABSTRACT: Introduction of exotic clones into the pedigree of commercial cashew clones could constitute a viable strategy to overcome the current low early nut yield and nut weight of the crop in West Africa. The aim of this study was to assess the combining abilities of Beninese, Brazilian and Ghanaian clones for early nut yield and nut weight. Twelve F1 hybrids were evaluated in the field for five traits such as stem diameter increment, canopy spread, nut yield, nut weight and cropping efficiency. Significant difference ( p ≤ .01) was observed for most of the traits. Nut weight varied from 5.3 to 10.1 g/year, whilst nut yield ranged from 666.1 to 872.8 kg/ha/year among the top five crosses in the third to fifth year after planting. The Beninese (BE) progenies were comparable to the Ghanaian (SG) progenies for early nut yield but inferior to the Ghanaian and Brazilian (A) progenies for nut weight. Pearson correlation coefficient estimate ( r = 0.74; p ≤ .01 ) suggest that, selecting for canopy spread in the north-south direction might improve early nut yield. GCA effects were more important than SCA effects. Narrow-sense heritability was moderate and exceeded 50% for all the traits. BE203 and SG224 showed positive GCA for early nut yield, whereas A2 and SG273 showed positive GCA for nut weight. Our study suggest that the Brazilian, Beninese and Ghanaian clones had different merits as potential parents for early nut yield and nut weight and could constitute a suitable genetic resource for improving cashew productivity.